Strike While the Iron Is Hot: Optimal Monetary Policy with a Nonlinear Phillips Curve - Peter Karadi; Anton Nakov; Galo Nu\~no; Ernesto Pastén; Dominik Thaler (CESifo GmbH, 2024)
We study the Ramsey optimal monetary policy within the Golosov and Lucas (2007) state-dependent pricing framework. The model provides micro-foundations for a nonlinear Phillips curve: the sensitivity of inflation to activity increases after large shocks due to an endogenous rise in the frequency of price changes, as observed during the recent inflation surge. In response to large cost-push shocks, optimal policy leverages the lower sacrifice ratio to reduce inflation and stabilize the frequency of price adjustments. When facing total factor productivity shocks, an efficient disturbance, the optimal policy commits to strict price stability, similar to the prescription in the standard Calvo (1983) model.
Keywords: E31; E32; E52; 330; state-dependent pricing; large shocks; nonlinear Phillips curve; optimal monetary policy